Identification of physical-spatial factors that can encourage walking on roads:: a case study in Avaré- SP - Massud, Nigme; Magagnin, Renata Cardoso (Technical and Scientific Journal Green Cities, 2021)
At present, a significant portion of movement in small and medium cities is made by foot. However, in most cities, many of the areas designated for pedestrian circulation have low quality of space, which has a negative impact on the promotion of walking. Considering this, this article aims to identify the physical and spatial factors that contribute towards encouraging walking on main streets. This case study was carried out on Major Rangel Avenue, located in the city of Avaré (SP). The methodology incorporated the use of the Walkability index (in Portuguese Índice de Caminhabilidade - iCam) (Index of Walkability, in English), developed by ITDP (2018). The analysis of the results showed that the evaluated segment has low quality for walkability, which is considered insufficient, requiring short-term actions to promote walkability in the location. The aspects which contribute negatively to walkability are associated with Attractiveness, Citizen Safety and Environment, which were considered insufficient. The use of ITDP’s method allowed to identify with greater fidelity the elements that contribute positively and negatively to turning the street more favorable to walking. KEY-WORDS: Walkability, Quality of space, Pedestrian.